RADIX ROC: a low complexity algorithm for the cell manufacturing design - Georges, Marcos Ricardo Rosa (2014)
The Cellular Manufacturing System has been widely used in industry as an alternative to increase the ability to compete. The benefits of the use of cellular manufacturing include increased flexibility, reduction of work in process and reducing the total processing time. The first step in the adoption of cellular manufacturing industries is in the design of the cell, which is made from an analysis of the incidence matrix. There are several algorithms to perform the analysis of this matrix to seek groups that may provide sources of manufacturing cells. This article proposes an algorithm of low computational complexity called RADIX ROC. This algorithm is based on the classic algorithm ROC (Rank Order Clustering). A comparative analysis of some algorithms is done at the end to demonstrate the low complexity of the algorithm and a review of the literature on the subject completes this work.